1196 Sonographic Assessment Versus Direct Clinical Measurement of Sialolith Size and Its Influence on Modality of Endoscopic Removal. (12th October 2021) - Pepper, T; Karia, R; Ryba, F
Abstract: Aim: The aim of this retrospective case series was to investigate the influence of sialolith size on the potential for endoscopic stone removal. Method: The records of 52 patients who underwent salivary endoscopy between September 2018 and February 2020 were reviewed. Included cases presented with at least one symptomatic major salivary gland, and sonographic or radiographic evidence of stone disease. Results: A total of 25 patients (48%) and 27 stones were identified. These patients had a mean age of 45.2 years (range 16–72); 52% were female. Most cases (19/25) involved the submandibular gland, with a virtually even division between left and right sides. The overall success rate of sialendoscopic retrieval was 23/27 (85%), with 17/27 stones removed intact and 6/27 undergoing fragmentation with an intraoral salivary pneumatic lithotripter (Cook Medical). Median (sonographic) stone size in the largest dimension for those stones removed intact was 4mm (range 3-12mm), while for those undergoing fragmentation it was 7mm (range 3-11mm). Ultrasound provided an accurate assessment of stone size in most cases, but underestimated diameter by an average of 1mm in 6/27 cases, and overestimated size by 1mm in a single case. Conclusions: Sialendoscopic stone retrieval is a minimally invasive and effective treatment for sialolithiasis. It is possible to remove most stones using a basket, with intraoral lithotripsy employed for larger stones. Ultrasound is a reliable diagnostic tool for predicting stone size but may underestimate size in a small proportion of cases.